Pengaruh Kepemilikan Institusional Dan Ukuran Perusahaan Terhadap Integritas Laporan Keuangan Pada Perusahaan Property Dan Real Estate - Muhammad Rivandi; Muhammad Hanif Pramudia (Forum Inovasi Bisnis dan Manajemen, 2022)
Integrity of financial statements is the presentation of financial statements correctly and honestly without anything being hidden. In order for information to be useful, financial statements must also be reliable, information is said to be reliable if the information is not misleading, so that users of financial statements are not wrong in making decisions.The purpose of this study was to determine the effect of institutional ownership and company size on the integrity of financial statements in property and real estate companies listed on the Indonesian stock exchange in 2018-2020.The method used in this research is quantitative. Sampling in this study using purposive sampling and obtained 55 companies. The analysis technique in this research is panel data regression.Based on the results of the study, all independent variables have a simultaneous effect on the integrity of financial statements. Partially, institutional ownership has no effect on the integrity of financial statements. While the size of the company has a positive effect on the integrity of financial statements.